2016
DOI: 10.1007/s11002-016-9400-7
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling country-of-origin effects: the interplay of product ethnicity, national identity, and consumer ethnocentrism

Abstract: International audienceThe country-of-origin (COO) of products has been shown to affect consumer choice, especially in situations where the origin has a stereotypical association with particular products and depending on certain consumer traits (e.g., national identity, consumer ethnocentrism). However, little is known about how these phenomena are related. Two controlled experiments conducted in two different countries and product categories reveal that product ethnicity moderates the impact of national identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 46 publications
5
47
0
3
Order By: Relevance
“…Research regarding the way consumers perceive and evaluate a product revealed that when consumers are processing products' COO information they tend to rely on three mechanisms: cognitive, affective, and normative (Table 1) (Johansson, 1989;Obermiller & Spangenberg, 1989). As a result, these three processes seem to influence consumers' perception about the overall evaluation of the products (Johansson, 1989;Obermiller & Spangenberg, 1989;Fischer, 2017). Country of origin is used as a "signal" for overall product quality and quality attributes, such as reliability and durability (Li & Wyer, 1994;Steenkamp, 1989).…”
Section: The Coo Effect On Consumers' Information Processing Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research regarding the way consumers perceive and evaluate a product revealed that when consumers are processing products' COO information they tend to rely on three mechanisms: cognitive, affective, and normative (Table 1) (Johansson, 1989;Obermiller & Spangenberg, 1989). As a result, these three processes seem to influence consumers' perception about the overall evaluation of the products (Johansson, 1989;Obermiller & Spangenberg, 1989;Fischer, 2017). Country of origin is used as a "signal" for overall product quality and quality attributes, such as reliability and durability (Li & Wyer, 1994;Steenkamp, 1989).…”
Section: The Coo Effect On Consumers' Information Processing Mechanismsmentioning
confidence: 99%
“…In the case of cognitive process, scholars argue that it is used as a cue, a signal, of the quality of the products (Bloemer, Brijs, & Kasper, 2009;Fischer, 2017), even though this mechanism may also be associated with emotions, pride, status, authenticity, as well as identity or other attributes related to consumers' selfexpression (Fischer, 2017). Hence, apart from the intrinsic cues that are associated with the physical characteristics of the products, consumers may also use extrinsic cues like COO during their information processing (Veale, 2006).…”
Section: Consumers Hold Social and Personal Norms Related To Coomentioning
confidence: 99%
See 1 more Smart Citation
“…It is an economically motivated form of domestic country bias (Zeugner-Roth, Zabkar, & Diamantopoulos, 2015) that results in a negative disposition towards non-domestic markets, products and brands (Carpenter, Moore, Alexander, & Doherty, 2013). Highly ethnocentric consumers will disregard other criteria such as price and quality in their decision making (Fischer & Zeugner-Roth, 2016) and have a tendency to overestimate domestic product quality whilst doing the opposite for foreign offerings (Klein & Ettensoe, 1999). As well as representing an economic threat, foreign products may also be viewed as a form of cultural menace (Cleveland et al, 2009).…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%
“…: Schooler, 1965;Han, 1989;Roth & Romeo, 1992;Martin & Eroglu, 1993;Papadopoulos & Heslop, 2003;Usunier, 2006;Zeugner-Roth & Diamantopoulos, 2009) and is continuing to receive great attention by academics (e.g. : Zeugner -Roth, Žabkar & Diamantopoulos, 2015;Fischer & Zeugner-Roth, 2017;Motsi & Park, 2019). Nevertheless, this is a very complex and fragmented research area and further studies are needed in order to increase the academic knowledge on the phenomenon (Verlegh & Steenkamp, 1999).…”
Section: Introductionmentioning
confidence: 99%